Changes in Subantarctic Heard Island Vegetation at Sites Occupied by Poa annua , 1987-2000 - JJ Scott; James Kirkpatrick (2005)
Poa annua, the only alien plant species recorded on subantarctic Heard Island, considerably expanded its range and abundance along three transects in tundra-like vegetation on the island in the period 1987-2000. This expansion was strongly associated with increased seal disturbance, which also favored Callitriche antarctica and damaged Pringlea antiscorbutica, leading to a decrease in mean vegetation height. Expansions of Azorella selago and Poa cookii were independent of the expansion of P. annua, relating to colonization of moraines. There was no evidence of displacement of other taxa by Poa annua in areas undisturbed by seals. Â© 2005 Regents of the University of Colorado.